PHYTOCHEMICAL INVESTIGATION AND IN VITRO EVALUATION OF HYPOGLYCEMIC POTENTIAL OF GREWIA HIRSUTA - N.ABIRAMI,; B.NATARAJAN,; E.SAGADEVAN, (International Journal of Pharma and Bio Sciences, 2014)
Diabetes is a metabolic disorder which results due to deficiency in insulin and its metabolism. A search for effective medication with lesser or no side effects is the need of the hour. Hence the current study is focused at evaluating the anti-diabetic potential of Grewia hirsuta. The leaves of G. hirsuta were subjected to solvent extraction with methanol, ethyl acetate and hexane and analyzed by various in vitro assays such as inhibition of carbohydrate digesting enzymes, non-enzymatic glycosylation of hemoglobin, glucose diffusion and uptake of glucose by yeast cells. The best screened extract was further evaluated for it phytochemical profile by qualitative and quantitative phytochemical analysis. The extract was also subjected to TLC. The results of the study suggest that Grewia hirsuta possesses significant hypoglycemic potential. With further mechanistic studies it can be proved as a better source of natural anti-diabetic agents.